PERAN KELOMPOK WANITA TANI DALAM PENINGKATAN PENDAPATAN RUMAH TANGGA PADA KELOMPOK WANITA TANI REJOSARI - Hari Gunawan; Ign Suprih Sudrajat; Wahyu Setya Ratri (JURNAL ILMIAH AGRITAS, 2025)
This study aims to determine the role of Kelompok Wanita Tani in increasing household income. The research was conducted at Rejosari Women Farmers Group, Depok, Sleman, Yogyakarta Special Region. The research used a quantitative analysis method. Sampling with a census sampling model of 31 respondents. In this study we use primary data and secondary data. The method of data analysis in this study is to use simple linear regression analysis with the test of the coefficient of determination (R2) and hypothesis testing using the statistical t-test, to determine the effect of the independent variable KWT role (X) on the dependent variable of increasing household income (Y). There are various indicators of the role of farm women's groups, namely, learning classes, cooperation vehicles, and production units. The results of this study indicate that the overall variable role of KWT (X) is still relatively low towards increasing household income (Y) with a coefficient value of 0.237 and the results of the statistical t test on the learning class indicator show a sig value of 0.031, the indicator of the vehicle of cooperation of 0.365 and the production unit shows a sig value of 0.698. That way, the role of farm women's groups in the learning class indicator has a role in increasing household income. The cooperation vehicle indicator has not played a role in increasing household income, and the production unit indicator has also not played a role in increasing household income.